Efektivitas Penggunaan E-Modul Pembelajaraan Bahasa Indonesia Terhadap Hasil Belajar Menulis Teks Deskripsi Siswa Kelas VII - Kharimah, Andi Nurul; Idawati, Idawati; Sakaria, Sakaria (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study aims to describe the effectiveness of e-modules on the learning outcomes of writing descriptive texts in class VII UPT SMPN Satap Lebo No. 24 Kepulauan Selayar students. This research is a type of experimental research. The data in this study are quantitative data from the results of students' pretest and posttest. The sample in this study amounted to 20 students. The results of data analysis show that the results of hypothesis testing from the results of data analysis of students' pretests and posttests show that the results of t count ≥ t table, namely 6.469 ≥ 2.093, it can be concluded that the hypothesis is accepted, namely the use of e-modules is effective in improving learning outcomes in writing descriptive texts of class VII UPT SMPN Satap Lebo No.24 Kepulauan Selayar students.